Ferdo se uči o sebi in drugih: Socialno in čustveno učenje s pomočjo likovne umetnosti - Batič, Janja; Košir, Katja (2020)
Ferdo is Learning About Himself and Others: Social and Emotional Learning with the Help of Fine Art. The handbook consists of a theoretical part and twenty practical activities. The theoretical part includes the definition of the SEL model, instructions for use of the manual and guidelines for the promotion of social and emotional learning in children. The starting points for the activities are works of art from the collection of the Maribor Art Gallery. By looking at works of art, talking about them and practical art activities, children learn to express their emotions and feelings. The handbook is the result of the Students Innovative Projects for the Benefit of Society 2016–2020 entitled Social and Emotional Learning through Fine Arts - SELUM.
Keywords: Social and emotional learning (SEL); social and emotional skills; strengthening and developing skills; fine arts; art activities